Proteomic and metabolomic approaches unveil relevant biochemical changes in carbohydrate and cell wall metabolisms of two blueberry (Vaccinium corymbosum) varieties with different quality attributes - Montecchiarini, Marina Lucía; Margarit, Ezequiel; Morales, Luisina Lourdes; Rivadeneira, Maria Fernanda; Bello, Fernando; Gollan, Agustín María; Vazquez, Daniel Eduardo; Podesta, Florencio Esteban; Tripodi, Karina Eva Josefina (Elsevier, 2019)
Quality maintenance in rapidly decaying fruit such as blueberries (Vaccinium corymbosum) is of essential importance to guarantee the economic success of the crop. Fruit quality is a multifaceted subject that encompasses flavor, aroma, visual and physical issues as main factors. In this paper we report an ample characterization of different biochemical and physical aspects in two varieties (O'Neal and Emerald) of blueberries that differ in firmness, aspect, flavor and harvesting times, at two different phenological stages (fruit set vs. ripe), with the intention of unveiling how the metabolic signature of each contributes to their contrasting quality. To this effect a metabolomic, ionomic and proteomic approach was selected. The results presented here show marked differences in several variables at the two stages and between varieties. Emerald is an early variety with a large, good taste and firm fruit, while O'Neal is soft, medium sized and very sweet. Proteomic data comparison between both cultivars showed that, at fruit set, processes related with the response to inorganic compounds and small molecule metabolisms are relevant in both varieties. However, solute accumulation (mainly amino acids and organic acids), enzymes related with C: N balance, water transport and cell wall recycling are enhanced in Emerald. In ripe fruit, Emerald showed an enrichment of proteins associated with TCA, nitrogen, small molecules and cell wall in muro recycling processes, while mannitol and fatty acid metabolism were enhanced in the soft variety. The measured variation in metabolite levels gave strong support to the precedent results. This study suggests that at fruit set, a composite scenario of active metabolic recycling of the cell wall, improved C: N balance and solute accumulation give place to a more efficient carbon and water resource management. During the ripe stage, an increased and efficient in muro and metabolic recycling of the cell wall, added to enhanced inositol and secondary metabolism may be responsible for a best turgor conservation in Emerald. These findings may yield clues for improvements in fertilization practices, as well as to assist the guided development of new varieties based on biochemical quality.